Інформація в Інтернеті та етнологія: інтерпретація весільного обряду - Шидішкене, І. (Народна творчість та етнологія, 2011)
The problem is the kind of online reader’s identification with heritage and environmental guidelines. The paper aims to reveal the educationally, reliability of the ethnological scientific publications excerpts published in websites and online populist articles about Lithuanian wedding ceremonies, and discuss how the online readers accept the information.